Being better by being right: subjective group dynamics and derogation of in-group deviants when generic norms are undermined - José M. Marques (2001)
The authors predicted that derogation of group deviants depends on the extent to which in-group norms or values are validated or undermined in a social context. In Experiment I participants were less tolerant and derogated in-group deviants more when other in-group members opposed the norm. In Experiment 2 participants derogated in-group deviants more than out-group deviants and than noncategorized individuals, but only when normative in-group members lacked uniformity. In Experiment 3 participants derogated in-group deviants more when there was uncertainty about in-group superiority. These results are consistent with previous research on the black sheep effect (J. M. Marques, V. Y. Yzerbyt, & J.-P. Leyens, 1988) and with the model of subjective group dynamics (D. Abrams, J. M. Marques, N. J. Bown, & M. Henson, 2000; J. M. Marques, D. Abrams, D. Paez, & C. Martinez-Taboada, 1998).